2008
DOI: 10.1002/cbdv.200890067
|View full text |Cite
|
Sign up to set email alerts
|

Ecdysteroids from Vitex Species: Distribution and Compilation of Their 13C‐NMR Spectral Data

Abstract: Iridoids and ecdysteroids are found in some genera of the family Verbenaceae. In such cases, they are used as chemotaxonomic markers for the difficult task of taxonomic identification by using morphological characteristics of plants belonging to this family. The present work describes the distribution of ecdysteroids in plants from the genus Vitex from a review of previous work on seventeen Vitex species. In addition, (13)C-NMR data of the main ecdysteroids found in this genus are described. This study attempt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 30 publications
3
14
0
1
Order By: Relevance
“…Interestingly, a literature search revealed that the side-chain configuration for a number of ecdysteroids, especially with two methylene groups in the side-chain, has only been assigned tentatively. [24,27] In the past, differences in chemical shifts were used to identify the configuration at C-24. [28] However, some ecdysteroids show negligible differences in their 13 C chemical shifts even though they represent epimers (e.g., 20,26-dihydroxyecdysone).…”
Section: Configuration Of the Side-chainmentioning
confidence: 99%
“…Interestingly, a literature search revealed that the side-chain configuration for a number of ecdysteroids, especially with two methylene groups in the side-chain, has only been assigned tentatively. [24,27] In the past, differences in chemical shifts were used to identify the configuration at C-24. [28] However, some ecdysteroids show negligible differences in their 13 C chemical shifts even though they represent epimers (e.g., 20,26-dihydroxyecdysone).…”
Section: Configuration Of the Side-chainmentioning
confidence: 99%
“…For both the chemical compound and genetic markers evaluated by clustering ( Figures 1 , 3 ), V. gardneriana was isolated from the other three species. This may be related to genotypic differences for this species, as it is found in a different biome ( Sena Filho et al, 2008 ) which may influence the expression of genes used for synthesis of chemical compounds. The use of two data tools (chemical and genetic diversity) more thoroughly supports systematic characterization of the species studied ( Rahalia et al, 2016 ), and validates our chemical marker proposal for the Vitex genus, namely, using the sesquiterpene skeleton with seven member rings as a biomarker candidate.…”
Section: Discussionmentioning
confidence: 99%
“…2). Структура и результат исследования показывают, что действие Мастодинона сравнимо с действием бромокриптина [7].…”
Section: опухоли женской репродуктивной системы Tumors Of Female Reprunclassified